2017
DOI: 10.4236/me.2017.87065
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Public Weather Services by Users in the Formal Services Sector in Accra, Ghana

Abstract: We undertook a study that evaluated the public weather services used by people working in the formal services sector of the Ghana based in Accra, the capital city of Ghana. The study employed randomly-sampling survey technique to request information from 102 respondents on their use of services and information produced by the Ghana Meteorological Agency (GMet), the country's official producer and archival of meteorological data, information, products and services. The results of the analysis of survey data ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Thus, the economic value of the national meteorological service to the national population was 444.9 million US dollars per year. A related study by Anaman et al [8] used CVM to estimate the economic value of public weather services produced by the Ghana Meteorological Agency (GMet) to users in the Formal Services Sector in Accra. The empirical results showed that the average WTP per person per year was 51.96 US dollars.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the economic value of the national meteorological service to the national population was 444.9 million US dollars per year. A related study by Anaman et al [8] used CVM to estimate the economic value of public weather services produced by the Ghana Meteorological Agency (GMet) to users in the Formal Services Sector in Accra. The empirical results showed that the average WTP per person per year was 51.96 US dollars.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The World Meteorology Organization (WMO) has suggested five priority areas for global concerns in its Global Framework for Climate Changes (GFCS), including agriculture and food security, disaster risk reduction, health, water, and energy [1] (pp. [5][6][7][8][9][10][11][12][13][14]. As agricultural production activities are sensitive to weather and climate conditions, meteorological information services are more important for agricultural decision-makers than those in other sectors.…”
Section: Introductionmentioning
confidence: 99%
“…The positive economic growth over the 1992 to 2006 period also led to positive real per capita GDP as the economic growth outweighed the population growth rate. In Ghana, economic growth generally slows down due to economic shocks such as the El-Nino weather phenomenon (Anaman et al, 2017). Over this period, the El Nino phenomenon was partly responsible for reduced growth rates during 1999, 2007, 2014 and 2015. Over the 25-year period from 1992 to 2016, there was positive economic growth measured by the growth of real GDP.…”
Section: Economic Growthmentioning
confidence: 99%
“…For example, in 2017, government total capital expenditures as a proportion of GDP was only 3.1%, the lowest in 25 years (refer to Figure 1 for more details), with only about one-sixth (0.5% of GDP) of the capital expenditures financed through domestic government sources, the remaining five-sixths (2.6% of GDP) in 2017 were financed with foreign grants and loans. In addition to election-related excessive spending, the more recent weak macroeconomic position of the country was also caused partly by the end of the decade-long international commodity price boom that occurred during the first decade of the 21 st Century, reduced levels of grants and gifts from Ghana's development partners from 2013 onwards, and the severe form of the El Nino weather phenomenon that affected the country in 2007and 2015(Anaman et al, 2017, which resulted in reduced production from the country's three hydro-electric dams, a major source of 2 One US dollar was worth about 4.85 Ghana cedis in the inter-bank exchange market as at the end of December 2018. electricity energy production in the country.…”
mentioning
confidence: 99%
“…Weather-related shocks also affect the economy. These include the dramatic changes in weather and climate variability related to the El Nino weather phenomenon observed in 1962/63, 1977/78, 1982/83, 2003, 2006/2007/2015(Ofori-Sarpong and Annor, 2012Economist Magazine, 2015;Anaman et al, 2017). Further, there have also been increasing average temperatures and decreasing rainfall possibly due to climate change.…”
Section: Problem Statementmentioning
confidence: 99%